2005
DOI: 10.1096/fj.04-2774fje
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of NOX‐2‐containing NADPH oxidase in early ischemic preconditioning

Abstract: Reactive oxygen species (ROS)‐mediated signaling is implicated in early ischemic preconditioning (PC). A NOX‐2‐containing NADPH oxidase is a recognized major source of ROS in cardiac myocytes, whose activity is augmented by preconditioning mimetics, such as angiotensin II. We hypothesized that this oxidase is an essential source of ROS in PC. Hearts from wild‐type (WT) and NOX‐2 knockout (KO) mice were Langendorff perfused and subjected to 35 min ischemia/reperfusion with or without preceding PC or drug treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 41 publications
(52 reference statements)
3
58
0
Order By: Relevance
“…The phosphorylation of p47 phox subunits induces their translocation from the cytosolic compartment to the cellular membrane, where they combine with other NADPH subunits to assemble the fully activated NADPH oxidase complexes that generate superoxide. Moreover, PKC-dependent activation of NADPH oxidase is reportedly involved in early ischemic preconditioning in the heart (2) and also in the action of ANG II in the regulation of neuronal activity in the brain (30). Several isoforms of PKC have been identified that phosphorylate the regulatory p47 phox subunits of NADPH oxidase to augment the production of superoxide radicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation of p47 phox subunits induces their translocation from the cytosolic compartment to the cellular membrane, where they combine with other NADPH subunits to assemble the fully activated NADPH oxidase complexes that generate superoxide. Moreover, PKC-dependent activation of NADPH oxidase is reportedly involved in early ischemic preconditioning in the heart (2) and also in the action of ANG II in the regulation of neuronal activity in the brain (30). Several isoforms of PKC have been identified that phosphorylate the regulatory p47 phox subunits of NADPH oxidase to augment the production of superoxide radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested a role for NADPH oxidase-derived ROS in cardiac pathology. Mice lacking gp91ds phox , a subunit of NADPH oxidase, do not develop ANG II-induced cardiac hypertrophy (2). On the other hand, excessive intracellular Ca 2ϩ accumulation is another factor mediating ischemia-induced cardiac injury.…”
mentioning
confidence: 99%
“…Reactive oxygen species (ROS) play a highly regulated role in normal physiological signalling and are involved in cellular adaptions to cellular stress (for example, gp91 phox NADPH oxidase-linked ischaemic conditioning 5 ). However, excess ROS production leads to pathological states such as heart failure and exacerbation of ischaemic cell death as occurs in ischaemia/reperfusion injury and heart failure.…”
Section: ) the Interaction Between Sglt1/smit And Gp91 Phox Nadph Oxmentioning
confidence: 99%
“…While mitochondrial-derived ROS are widely considered to be involved in the pathway, there is also evidence for a signaling role of NADPH oxidase-derived ROS in the proximal pathways of preconditioning. Bell et al [110] studied ischemic preconditioning in isolated buffer-perfused hearts from mice with a global deficiency of Nox2 (Nox2−/− mice) and matched wild-type mice, and showed that Nox2 knockout mice failed to precondition in response to brief global ischemia. In contrast, hearts of wild-type mice had enhanced NADPH oxidase activity and showed attenuated infarct sizes after preconditioning.…”
Section: Ischemic Preconditioningmentioning
confidence: 99%
“…Further investigation into the signaling mechanisms involved in the above effects revealed that protein kinase C was essential for the activation of Nox2 oxidase in ischemic preconditioning [110]. In angiotensin II-dependent preconditioning, NADPH oxidase-induced activation of ASK-1 and p38MAPK were suggested to trigger mitochondrial ROS generation and consequent cardioprotection [111], whilst in tachycardia/exercise-mediated preconditioning NADPH oxidase-induced modulation of SR Ca2+ release was proposed as the mechanism mediating the protective response [44].…”
Section: Ischemic Preconditioningmentioning
confidence: 99%